Empowering Employees to Prevent Fraud in Nonprofit Organizations - Bradley, John M. (2015)
This Article examines the significant problem of fraud within nonprofit organizations and demonstrates that current anti-fraud measures do not adequately reflect the important role employees play in perpetuating or stopping fraudulent activity. Psychological and organizational behavior studies have established the importance of (1) participation and (2) peers in shaping the behavior of individuals within the organizational context. This Article builds on that research and establishes that to successfully combat fraud, organizations must integrate employees into the design, implementation, and enforcement of anti-fraud strategy and procedures. Engaged, empowered employees will be less likely to commit fraud and more likely to dissuade their peers from fraudulent behavior. After examining the theory underlying the proposed approach, this Article sets forth directions and specific suggestions for designing an anti-fraud program that empowers employees